EU General Data Protection Regulation (GDPR) - An Implementation and Compliance Guide (3rd Edition) - Governance, IT (IT Governance Publishing, 2019)
EU GDPR - An Implementation and Compliance Guide is a perfect companion for anyone managing a GDPR compliance project. It explains the changes you need to make to your data protection and information security regimes and tells you exactly what you need to do to avoid severe financial penalties.